“Candidatum”. Representations about the political representation fuction in the early 20th century in Chile - Jara, René (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
The present study analyzes the problem of representation politics from the studies of the visual and the visual. Starting off of the illustrations of candidates published in a corpus of Chilean magazines of the beginning of the century, work install the question by the permanent questioning of the media to the very constitution of this social agency. The doubts and uncertainties that the installation of an electoral democracy are collected by a series of caricaturists between 1906 and 1920, in a genre particular of illustrated magazines. In this article, we analyze the most significant images of this corpus, which express at the same time the virtues and vices of the candidate’s exercise, as well as the tensions that accompany the appearance of electoral democracy in the Chilean political landscape.